APPLICATION OF ONLINE PLATFORMS IN TRAINING FOR THE DEVELOPMENT OF PROFESSIONAL DIGITAL COMPETENCES (Innovation in Woodworking Industry and Engineering design, 2026)
In the conditions of a global economy and an explosion of digital and online technologies, educational institutions must respond adequately by producing well-trained professionals with both professional and digital competencies. The digital competences of each person are an indicator of his successful realization in the professional sphere. The report provides an overview of training at the Forestry University in Sofia, Bulgaria. To assess the extent to which secondyear Engineering Design (Interior and Furniture Design) students possess the necessary skills and digital professional competencies when working with unfamiliar online software, they were given the task of creating a 3D design of an apartment consisting of a living room with kitchenette and bathroom using Roomstyler's 3D planning tool. In the process of work, the student's digital knowledge and skills are evaluated. Participants in the assignment were also asked to complete an anonymous online survey to examine their satisfaction and attitude to work with novel software.